A Web‐Based Survey of Erection Hardness Score and Its Relationship to Aging, Sexual Behavior, Confidence, and Risk Factors in Japan. Issue 2 (3rd October 2013) - Kimura, Masaki; Shimura, Satoru; Tai, Toshihiro; Kobayashi, Hideyuki; Baba, Shiro; Kano, Munehide; Nagao, Koichi
Abstract Introduction Erection hardness is an elemental component of men's sexual quality of life that can be easily measured by the Erection Hardness Score (EHS). However, there are few published data regarding EHS, and there is little understanding of its relationships to aging, men's sexual behavior, sexual confidence, and risk factors in Japan. Aim To assess EHS and how it correlates to aging, sexual behaviors, sexual self‐confidence, and risk factors in a Japanese population database. Methods A web‐based cross‐sectional nationwide survey conducted between March and May 2009 in Japan. Main Outcome Measures EHS, lifestyle factors, comorbidities, general health, sexual confidence, frequency of sexual behaviors, and attitudes toward treatment of erectile dysfunction (ED). Results A total of 7, 710 men with a mean age of 39.3 ± 13.0 years participated in this survey. In 6, 528 participants who were not using phosphodiesterase type 5 inhibitors, 3, 540 (54.2%) had EHS ≤ 3 and 1, 196 (18.3%) had EHS ≤ 2. We found a significant age‐dependent decrease in EHS, sexual confidence, and frequency of sexual activities. Sexual confidence was strongly associated with higher EHS but was also associated with older age groups, presence of offspring, awareness of better general health, and greater frequency of sexual activity. In age‐adjusted multivariate logistic regression, risk factors for a lower EHS (defined as EHS ≤ 2) were heavy smoking, which was defined as more than two packs per day (odds ratio [OR], 1.7) or a history of metabolic syndrome (OR, 1.4), hypertension (OR, 1.2), and diabetes mellitus (OR, 1.4). Conclusions EHS correlates to various elements, such as aging, sexual behaviors, sexual confidence, and ED‐related risk factors, and can be a valuable tool in clinical practice for monitoring and treating ED and thereby improving the quality of life for men and their sexual partners. Kimura M, Shimura S, Tai T, Kobayashi H, Baba S, Kano M, and Nagao K. A web‐based survey of Erection Hardness Score and its relationship to aging, sexual behavior, confidence, and risk factors in Japan. Sex Med 2013;1:76–86.